Wonders in the sky unexplained aerial objects from antiquity to modern times and their impact on human culture, history, and beliefs - Vallee, Jacques; Aubeck, Chris (Jeremy P. Tarcher / Penguin a member of Penguin Group (USA) Inc., 2010)
In Wonders in the Sky, respected researchers Jacques Vallee and Chris Aubeck examine more than 500 selected reports of sightings from biblical-age antiquity through the year 1879-the point at which the Industrial Revolution deeply changed the nature of human society, and the skies began to open to airplanes, dirigibles, rockets, and other opportunities for misinterpretation represented by military prototypes. Using vivid and engaging case studies, and more than seventy-five illustrations, they reveal that unidentified flying objects have had a major impact not only on popular culture but on our history, on our religion, and on the models of the world humanity has formed from deepest antiquity.